ABERMES & PARADIGMA KOMUNIKASI - nurkholisoh, nurkholisoh (Universitas Prof. Dr. Moestopo (Beragama), 2006)
Like Horkheimer, habermas contends that knowledge is historically rooted and interest bound. But he understands this in quite different terms form his predecesoor. In Knowledge an Human Interest and Theory and Practice, Habermas develops the theory of cognitive interest(or knowledge-constitutive interests), the importent first stage in his elaboration of the relationship of knowledge to human activity. In more recent work he has extended this inquiry and formulated the theory of âcommunitave competenceâ . This complex theories have been developed in order to justify the critical enterprise. In this theory Habermas argues that all speech is oriented to the idea of a genuine consensus â a discursively achieved consensus â which is rarely realized.